Cyber-physical systems integrated computing and engineering design - Hu, Fei 1972- (CRC Press, 2014)
"Many things need to be done to realize the benefits of cyber-physical systems. With these goals for CPS improvement, the book discusses the many challenges that must first be overcome, and provides a roadmap on how to do it. Accounting for random events that can occur in a real environment can be troublesome for a system when trying to ensure safety, security, and predictability"--
Includes bibliographical references. - Print version record
Keywords: Automatic control; Cybernetics; Systems engineering; Commande automatique; Cybernétique; Ingénierie des systèmes; cybernetics; systems engineering; COMPUTERS; Security; General; TECHNOLOGY & ENGINEERING; Electrical; TECHNOLOGY & ENGINEERING; Mobile & Wireless Communications; TECHNOLOGY & ENGINEERING; Engineering (General)